TRIMETAZIDINE MR EFFECTS ON THE PARAMETERS OF 24-HOUR ELECTROCARDIOGRAM MONITORING AND HEART RATE VARIABILITY - M. V. Novikova; M. G. Glezer (Кардиоваскулярная терапия и профилактика, 2013)
Aim. To assess the effects of the four-month trimetazidine MR therapy on the parameters of 24-hour electrocardiogram (ECG) monitoring and heart rate variability (HRV) in patients with stable coronary heart disease (CHD).Material and methods. This prospective, non-randomised study, with the inclusion of 66 consecutive patients who had stable CHD and stable stress test results, investigated the effects of trimetazidine MR therapy on the parameters of 24-hour ECG monitoring and HRV.Results. Trimetazidine MR did not markedly affect the 24-hour, daytime, or nighttime levels of heart rate. Trimetazidine MR therapy was not associated with any substantial changes in frequency and time-domain HRV parameters or in the incidence of cardiac arrhythmias. However, there was a significant reduction in the number of patients with ST segment depression (from 66,7% to 43,8%; p<0,001) and in the duration of ischemic episodes (from 10 (6,2;21) minutes to 7,42 (5;12,3) minutes (p=0,025)).Conclusion. Adding trimetazidine MR to the treatment of patients with stable CHD provides an additional beneficial antiischemic effect.